If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6x = 10 + -5 Combine like terms: 10 + -5 = 5 12 + -6x = 5 Solving 12 + -6x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = 5 + -12 -6x = 5 + -12 Combine like terms: 5 + -12 = -7 -6x = -7 Divide each side by '-6'. x = 1.166666667 Simplifying x = 1.166666667
| y^2+2y-9= | | h=-16t^2+90t | | y-100=-9.5(x-0) | | 106=-16+90 | | 7x+2=61 | | x^2+-10x+21=0 | | -3=2x-13 | | 260000-x(.2)=50440 | | (n+1)*((n+1)-2)=60 | | -5x+8=3 | | 4x+9x+2x=180 | | -(d+7)+4d-7=3d-7 | | -4y+6=-6y-8 | | -9b-4=-67 | | 21+X^2+-10x=0 | | -x-3=-10x-12 | | x^2-3x+5.5=0 | | y-40=-5.25(x-20) | | y=8/6 | | 260000-x(.20)=50440 | | -(x+7)=8x-25 | | 105-(4x+14)=4(x+7)+x | | 4m=925 | | -5(4b+2)+(21b-8)=0 | | 15=3x+6 | | -2a+2(3a-4)=24 | | -3y-5y=10 | | 4x-6y=27 | | y-96=-3(x-32) | | 4x^2-27x+7=-6x+2 | | 13=4x-10 | | (2x-2)+(7y+1)=145 |